Pengaruh Dukungan Keluarga terhadap Rendahnya Kunjungan K1 Murni (0-12 Minggu) di Desa Lomuli UPTD Puskesmas Lemito - Nita Ernawati; Widia Shofa Ilmiah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The initial antenatal care visit, known as K1 murni, conducted between 0 and 12 weeks of gestation, plays a pivotal role in identifying early pregnancy risks and establishing a foundation for continuous maternal care. However, in several rural areas such as Lomuli Village, the rate of K1 murni attendance remains low despite the presence of health facilities. This study aimed to examine the relationship between family support and early antenatal visit behavior among pregnant women. A quantitative approach was used with a cross-sectional design involving 34 respondents who met the inclusion criteria. Data were collected through structured questionnaires and analyzed using Kendall’s Tau-b correlation test. The findings show that most respondents who failed to attend the K1 visit belonged to the group reporting poor family support. The statistical analysis revealed a strong and statistically meaningful correlation, with a Tau-b coefficient of 0.866 and a p-value of 0.000. These results suggest that early antenatal behavior is deeply influenced by the social support system surrounding the pregnant woman, particularly within households where health-related decisions are shaped collectively. The study concludes that family involvement during early pregnancy enhances maternal compliance with antenatal services. Health promotion strategies must therefore explicitly integrate families as active participants in antenatal education and support.